Optical fiber vibration sensor network based on multi-service optical code-division multiple-access system - Kuje, Danjuma (2016)
Optical fiber sensors are used in the measurements of a number of different physical properties. Some areas of application of sensors include harsh and electromagnetic interference prone environments where electronics cannot survive and in distributed detection. Recent advancement in fiber optics technology has brought about the need for distributed vibration monitory in structures and equipment. This is essential in order to predict the unusual behaviors and forestall unforeseen corrective maintenance that may require total overhaul of such structures and equipment. Different multiplexing techniques have been used in distributed sensing which include Time Division Multiplexing (TDM), Wavelength Division Multiplexing (WDM) and Optical Code Division Multiplexing (OCDM). Some either suffered from low scanning speed such as in TDM or high cost of the multi-wavelength light source in WDM. OCDM is limited by Multiple Access Interference (MAI) which makes it difficult to differentiate the correct signal from the noise. Intensity modulated fiber vibration sensor multiplexing using Multi-Service (MS) code in Spectral Amplitude Coding- Optical Code Division Multiple Access (SAC-OCDMA) with Spectral Direct Decoding (SDD) was investigated in this work in order to reduce MAI impact with low cross correlation. The proposed work was implemented using a simulation tool to compare MS code with Khazani-Syed (KS) and Modified Quadratic Congruence (MQC) codes while laboratory experimental design was used to implement and compare the system with using MS and KS codes based on the level of power received. Due to cost of components and availability constrains, the MQC code was not implemented in the experiment. Results show frequency response being received at slightly higher peak power in vibration sensor multiplexing using MS code with power levels of 3.61dB and 10.43dB above noise level in back to back and over 25km fiber systems with average percentage improvement of 6.59% and 24.16%, 7.85% and 11.71% compared to 2.45dB and 4.81dB respectively obtained using KS code. The range of 0Hz - 212.1Hz frequency obtained from both system using MS and KS codes show the possibility of remote vibration monitoring in structures that exhibit low frequency such as bridges, transformers and pipelines.